The Impact of the COVID-19 Pandemic on Osteoporosis Patients - Gülnur Taşcı Bozbaş; Musa Dönmez; İmran Kurt Ömürlü; Gülcan Gürer (Galenos Yayinevi, 2023)
Objective: Osteoporosis is the most common metabolic bone disease associated with significant mortality and morbidity. The coronavirus disease-2019 (COVID-19) pandemic, which has affected the entire world, has necessitated curfews, quarantine measures, and alterations in hospital health services. Our study aimed to investigate the impact of the pandemic period on our osteoporosis patients. Materials and Methods: Ninety-two previously diagnosed osteoporosis postmenopausal female patients who presented to the outpatient clinic between July 20, 2020, and October 20, 2020, were enrolled in the study. Besides the patients' demographic characteristics, the duration of osteoporosis, the osteoporosis medications they used, and whether they interrupted the treatment during the pandemic period, and if they did, the reason was questioned. In addition, fracture history, fall frequency and exercise status were recorded before and during the pandemic. Results: The patients' mean age was 61±8 years. 10.9% had been exercising before the pandemic, and of these, 87.5% either reduced their exercise frequency or quit exercising during the pandemic. 20.7% of the patients before the pandemic and 17.4% during the pandemic period had a history of falling (p>0.05). When the continuation of osteoporosis treatment was analyzed, 7 (7.6%) patients were found to have interrupted their treatments during the pandemic. Of these, one of them had interrupted treatment due to the inability to obtain the medication, one of them had interrupted treatment due to not having the necessary investigations performed, and five patients had interrupted treatment because they could not leave their homes due to restrictions. It was observed that the interruption of drug treatment was not associated with those living in urban or countryside, or the level of osteoporosis knowledge (p>0.05). Conclusion: Our study demonstrated that the COVID-19 pandemic adversely affected osteoporosis patients' medication adherence and exercise levels. Therefore, we recommend taking preventive measures of addition existing ones in similar situations.